Very low concentrations of ethanol suppress excitatory synaptic transmission in rat visual cortex - Luong, Lucas (Eur J Neurosci, 2017)
Ethanol is one of the most commonly used substances in the world. Behavioral effects of alcohol are well described, however, cellular mechanisms of its action are poorly understood. There is an apparent contradiction between measurable behavioral changes produced by low concentrations of ethanol, and lack of evidence of synaptic changes at these concentrations. Furthermore, effects of ethanol on synaptic transmission in the neocortex are poorly understood. Here, we set to determine effects of ethanol on excitatory synaptic transmission in the neocortex. We show that 1–50 mM ethanol suppresses excitatory synaptic transmission to layer 2/3 pyramidal neurons in rat visual cortex in a concentration-dependent manner. To the best of our knowledge, this is the first demonstration of the effects of very low concentrations of ethanol (from 1 mM) on synaptic transmission in the neocortex. We further show that a selective antagonist of A(1) adenosine receptors, 8-cyclopentyl-1,3-dipropylxanthine (DPCPX), blocks effects of 1–10 mM ethanol on synaptic transmission. However, the reduction in excitatory postsynaptic potential amplitude by 50 mM ethanol was not affected by DPCPX. We propose that ethanol depresses excitatory synaptic transmission in the neocortex by at least two mechanisms, engaged at different concentrations: low concentrations of ethanol reduce synaptic transmission via A(1)R-dependent mechanism and involve presynaptic changes, while higher concentrations activate additional, adenosine-independent mechanisms with predominantly postsynaptic action. Involvement of adenosine signaling in mediating effects of low concentrations of ethanol may have important implications for understanding alcohol’s effects on brain function, and provide a mechanistic explanation to the interaction between alcohol and caffeine.